The oxidative stability of microalgae oil (Schizochytrium aggregatum) and its antioxidant activity after simulated gastrointestinal digestion: Relationship with constituents. Issue 12 (28th September 2015) - Lv, Junwei; Yang, Xianqing; Ma, Haixia; Hu, Xiao; Wei, Ya; Zhou, Wanjun; Li, Laihao
Abstract : The objective of this study was to examine the chemical composition and oxidative stability of microalgae oil, also to explore in vitro bioaccessibility and antioxidant activity of microalgae oil after simulated gastrointestinal digestion. In total, more than 50 fatty acids were identified by GC–MS analysis, with both palmitic acid (38.3%) and DHA (34.5%) being identified as major fatty acids. The contents of total phenolics and flavonoids in the various solvent extracts were measured spectrometrically, and their amounts were 39.33 ± 0.34 µg gallic acid/g and 16.08 ± 4.3 µg rutin/g, respectively. HPLC analysis showed that the contents of β‐carotene, α‐tocopherols, β‐ and γ‐tocopherols (not separated) and δ‐tocopherols were 136 µg/100 g, 164.4 µg/g, 317.3 µg/g, and 43.2 µg/g, respectively. Concerning sterols, cholesterol was the principal sterol at 4210.5 mg/kg and the other six main sterols were campesterol (121.4 mg/kg), 24‐methylene cholesterol (192.8 mg/kg), 24‐methyl‐colest‐7‐en‐3β‐ol (144.6 mg/kg), ergosterol (144.8 mg/kg), stigmasterol (260.1 mg/kg) and Δ7, 24‐stigmastadienol (150.5 mg/kg), respectively. The overall chemical properties of the tested oils indicated that microalgae oil had a great oil quality. A Schaal oven test was used to evaluate the oxidative stability of microalgae oil. Furthermore, in vitro simulated gastrointestinal digestion was performed, and the antioxidant ability of digestion oil was determined by using a 2, 2‐diphenyl‐1‐picrylhydrazyl (DPPH) radical‐scavenging assay, a 3‐ethylbenzothiazoline‐6‐sulfonic acid (ABTS) radical cation decolourisation activity assay, a reducing power assay, a β‐carotene bleaching assay and an oxygen radical absorbance capacity (ORAC) antioxidant assay. The results showed that following simulated gastrointestinal digestion, microalgae oil displayed a good in vitro bioaccessibility and moderate antioxidant capacity. Thus, the antioxidant activity of the microalgae oil was mainly contributed by its abundant antioxidant constituents. Practical applications: Schizochytrium aggregatum oil is a good source of DHA and of effective, bioaccessible antioxidants. The DPPH radical is rather stable, and our study used a relatively fast method for measuring both the hydrophilic and lipophilic substances during in vitro antioxidant activity. The change of violet colour to yellow during the DPPH assay is thought to be due to the attribution of hydrogen atoms by antioxidant substances. The extent of decolourisation is a significant indicator of the sample's antioxidant ability. As shown in figure that the scavenging abilities of all the samples were well correlated with increasing concentrations, and the scavenging activity of BHT was higher than that of microalgae oil. At concentrations ranging from 0.5 to 10 mg/mL, the DPPH radical scavenging ability of digestion oil was determined at 6.8–64.9%. Lower IC50 values indicated a higher radical scavenging activity. The IC50 value of microalgae oil in our DPPH radical scavenging study was 5.76 mg/mL, and solutions of BHT had an IC50 value of 0.56 mg/mL. Although microalgae oil was shown to be weaker than BHT, it demonstrated a fairly good scavenging ability. The DPPH radical scavenging abilities of digestion oil and BHT. Abstract : The DPPH radical is rather stable, and our study used a relatively fast method for measuring both the hydrophilic and lipophilic substances during in vitro antioxidant activity. The change of violet colour to yellow during the DPPH assay is thought to be due to the attribution of hydrogen atoms by antioxidant substances. The extent of decolourisation is a significant indicator of the sample's antioxidant ability. As shown in figure that the scavenging abilities of all the samples were well correlated with increasing concentrations, and the scavenging activity of BHT was higher than that of microalgae oil. At concentrations ranging from 0.5 to 10 mg/mL, the DPPH radical scavenging ability of digestion oil was determined at 6.8–64.9%. Lower IC50 values indicated a higher radical scavenging activity. The IC50 value of microalgae oil in our DPPH radical scavenging study was 5.76 mg/mL, and solutions of BHT had an IC50 value of 0.56 mg/mL. Although microalgae oil was shown to be weaker than BHT, it demonstrated a fairly good scavenging ability. The DPPH radical scavenging abilities of digestion oil and BHT.